Talent Management Focus on Small and Medium Enterprises A Systematic Literature Review - Fitri Novilia; Syamsul Hadi Senen (Westscience Press, 2023)
This systematic literature review explores the employee perspective on talent management within the context of Small and Medium Enterprises (SMEs) in Indonesia. Out of a total of 208 articles initially considered, the final analysis focuses on seven key articles for comparative evaluation. The research delves into various aspects of talent management, including recruitment strategies, employee development initiatives, and retention policies implemented by SMEs. The study aims to provide a comprehensive understanding of how talent management is perceived and experienced by employees in the unique setting of SMEs in Indonesia. By synthesizing findings from the selected articles, the review addresses crucial factors such as the role of technology, shifts in organizational culture, and specific challenges faced by employees in managing talent within SMEs. Through this systematic approach, the research contributes theoretical insights and practical implications for enhancing talent management practices in the SME sector. The findings aim to offer valuable guidance to SME leaders, human resource practitioners, and researchers seeking to optimize talent management strategies in the dynamic business landscape of Indonesia. The research that integrates the employee perspective into talent management is still relatively scarce, especially with a focus on small and medium-sized micro enterprises in Indonesia. This literature review specifically concentrates on the employee's standpoint within the context of talent management. A systematic literature review approach is employed in this study, assisted by the VOS Viewer application. The PRISMA method is used for the review. Out of the 154 Scopus articles reviewed, including empirical studies, conceptual articles, and book chapters, 7 articles specifically address the employee perspective in talent management research in SMEs. The literature review identifies that, although recent literature involves employees as key participants in strategic talent management, conceptual and empirical articles in this stream are still limited and require further conceptual and empirical development.